Entangled Animisms: Whakaaro and dialogue in the artwork of Shannon Te Ao. (18th August 2019) - Braddock, Christopher
Abstract : Inspired by the artworks of Shannon Te Ao to think through the problematic term 'animism', this article explores a Māori cosmological worldview (Te Ao Māori) especially with regard to the Māori faculty of whakaaro (thought or thinking) as well as exploring language and its utterance (kōrero). Shannon Te Ao recites on a cosmic level with ancestors, animals, plants and us, revealing non-anthropocentric rights and agency. Writing about animism from the shores of Aotearoa New Zealand creates compelling critique of historical ethnographic animism with its racist and scientifically driven evolutionist roots. From this vantage point, the work of quantum physicist David Bohm on quantum discontinuity and entanglement leads to a form of dialogue that resonates with Māori cosmologies and ontologies. Significantly, the nature of these 'entangled animisms' means resisting hierarchies and power dynamics at work between indigenous Māori worldviews and Euro-American concepts.